Bourdieu's Strategy in the Movie "A Bug's Life": An Application Of Pierre Bourdieu’s Theory (ELITE: Journal of English Language and Literature, 2022)
Movies have been a platform to picture every human-related activity. The movie is not a mere depiction but a reflection of social life. The idea is to set movies as a manifestation of social life. A Bug’s Life (1998) is an animated movie directed by John Lasseter which followed the storyline of Seven Samurai (1954) a movie by Akira Kurosawa. A bug’s life is a manifestation of social life, it contains the struggle for power, social dynamics, and oppression. This study aimed to analyze the depiction of the strategy of power by Pierre Bourdieu in A Bug’s life and focused only on the strategy-based practical action. Bourdieu has classified the strategy into two segments, those are reproduction strategy and reconversion strategy. The author used three variables to analyze the movie, those are Habitus, Capital/Modal, and Field, which determine the agent’s strategy. After conducting the research using Pierre Bourdieu's theory, the author found that a strategy is a tool of struggle, strategy is based on emergence, strategy is made to counter another strategy, and strategy is a manifestation of capital, habitus, and field.